Genomic and Physiological Basis of Structural and Foliar Trait Variation in Tropical Species Pterocarpus officinalis: Implications for Restoration in Future Drier Climates - Sean M. Collins; Kevin C. Grady; Gustavo P. Lorenzana; Kailey Baesen; Laura Figueroa‐Corona; E. Petter Axelsson; Aalap Dixit; Amanda R. De La Torre (Evolutionary Applications)
ABSTRACT Tropical wetlands are some of the most threatened ecosystems in the world. Pterocarpus officinalis exists in swampy wetlands in riparian and fresh‐water coastal areas across the neotropics, supporting biodiversity and storm surge and flooding protection as well as water filtration. In Puerto Rico, P. officinalis‐dominated forests have been severely declining in recent decades, mainly due to land development. Reversing this trend in the face of climate change and projected sea level rise via ecological restoration may benefit from understanding phenotypic traits suitable for future climates. Currently, there are no seed sourcing guidelines for restoration, due to the understudied nature of the species. The goals of our study were to examine population structure and the genomic basis of variation in structural and physiological foliar traits. Seeds were collected from twelve seed sources spanning the natural distribution of P. officinalis in Puerto Rico. Water use efficiency related foliar traits were measured in well‐watered conditions from seedlings grown in a nursery experiment. A total of 109 seedlings were whole‐genome resequenced from 12 seed sources. Our results indicate strong foliar trait variation despite very little genetic differentiation among seed sources within the island, suggesting a relatively small number of genes might be involved in water‐use efficiency traits. Eleven out of thirteen foliar traits varied significantly across seed sources. Trait variation was associated with either longitude, elevation, mean annual precipitation, or isothermality. Seedlings across seed sources were observed to have different strategies for managing water use. Candidate loci identified using Genome‐Wide Association Studies were associated with signal transduction, transcription regulation, DNA and RNA methylation, transport, and primary and secondary metabolism. Restoration of this species is key in maintaining ecosystem services. Our study identified seed sources that may be successful in drier restoration conditions and match future arid climates.